Leaf traits variation during leaf expansion in Quercus ilex L. - GRATANI, L.; Bonito, A. (Photosynthetica, 2009)
The morphological, anatomical and physiological variations of leaf traits were analysed during Quercus ilex L. leaf expansion. The leaf water content (LWC), leaf area relative growth rate (RGRl ) and leaf dry mass relative growth rate (RGRm) were the highest (76±2 %, 0.413 cm 2 cm –2 d –1 , 0.709 mg mg –1 d –1 , respectively) at the beginning of the leaf expansion process (7 days after bud break). Leaf expansion lasted 84±2 days when air temperature ranged from 13.3±0.8 to 27.6±0.9 °C. The net photosynthetic rate (PN), stomatal conductance (gs ), and chlorophyll content per fresh mass (Chl) increased during leaf expansion, having the highest values [12.62±1.64 µmol (CO2) m –2 s –1 , 0.090 mol (H2O) m –2 s –1 , and 1.03±0.08 mg g –1 ,respectively] 56 days after bud break. Chl was directly correlated with leaf dry mass (DM) and PN. The thickness of palisade parenchyma contributed to the total leaf thickness (263.1±1.5 μm) by 47 %, spongy layer thickness 38 %, adaxial epidermis and cuticle thickness 9 %, and abaxial epidermis and cuticle thickness 6 %. Variation in leaf size during leaf expansion might be attributed to a combination of cells density and length, and it is confirmed by the significant (p<0.001) correlations among these traits. Q. ilex leaves reached 90 % of their definitive structure before the most severe drought period (beginning of June – end of August). The high leaf mass area (LMA, 15.1±0.6 mg cm –2 ) at full leaf expansion was indicative of compact leaves (2028±100 cells mm –2 ). Air temperature increasing might shorten the favourable period for leaf expansion, thus changing the final amount of biomass per unit leaf area of Q. ilex.
Keywords: leaf anatomy; leaf expansion; leaf morphology; net photosynthetic rate; Quercus ilex

Forecasted stability of Mediterranean evergreen species considering global changes - GRATANI, L.; Bombelli, A. (GLOBAL CHANGE AND PROTECTED AREAS, 2001)
Plant communities of the Mediterranean climate Regions are exposed tohigh temperatures, high radiation and water stress during summer, they are dominated by evergreen sclerophyllous species and drought semi deciduous species. To define the adaptive strategies, anatomical and morphological leaf traits of Quercus ilex L., Phillyrea latifolia L. (typical evergreen sclerophyllous species) and Cistus incanus L., (a drought semi deciduous species), growing in the Mediterranean maquis along Pome's coast line (Italy) were analysed. The typical evergreen sclerophyllous species have long leaf life span (from 1 to 4 years), steeper leaf inclination (average 56 degrees), higher specific leaf mass (average 21.3 mg cm(-2)) and the highest leaf thickness (average 324 mum). The semi deciduous species have a lower leaf life span (from 4 to 8 months), a lower leaf inclination (44 degrees +/- 13 degrees), a lower specific leaf mass (14.7 +/-1.5 mg cm(-2)) and a lower leaf thickness (244 +/- 15 mum). The more xeromorphyc species (Q. ilex and P. latifolia) may be at a competitive advantage considering the forecasted air temperature increase in the Mediterranean basin. Increasing drought stress may in fact determine a shortening of leaf life span that may prove to be critical for C. incanus. Knowledge of plant response to stress factors is important in the perspective of climatic changes.
Meeting on Global Change and Protected Areas, LAQUILA, ITALY, SEP, 1999Meeting on Global Change and Protected Areas, LAQUILA, ITALY, SEP, 1999The following values have no corresponding Zotero field: periodical: GLOBAL CHANGE AND PROTECTED AREAS pub-location: PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS
Keywords: Q. ilex; P. latifolia; C. incanus; leaf life span

RESPONSE TO MICROCLIMATE OF MORPHOLOGICAL LEAF ATTRIBUTES, PHOTOSYNTHETIC AND WATER RELATIONS OF EVERGREEN SCLEROPHYLLOUS SHRUB SPECIES - GRATANI, L. (PHOTOSYNTHETICA, 1993)
Leaf adaptations of Quercus ilex L., Phillyrea latifolia L. and Pistacia lentiscus L. to various environmental conditions namely from the viewpoint of the differences of leaf area, dry mass, chlorophyll (Chl) content, sclerophylly index, succulence index and net photosynthetic rate (P(N)), are shown. Irradiance was the most important factor to influence P(N), leaf temperature, stomatal conductance (g(s) and transpiration rate (E). Under canopy layer low red-far red ratio reduced P(N). Shade leaves were enriched by Chl b. Chl content and sclerophylly index were good leaf characteristics to express adaptability of plants to microclimate.
The following values have no corresponding Zotero field: pub-location: NA KARLOVCE 1A, PRAGUE 6, CZECH REPUBLIC CS-160 00 publisher: INST EXPERIMENTAL BOTANY, ACAD SCI CZECH REPUBLIC
Keywords: irradiance; leaf area; microclimate; Phillyrea latifolia L.; Pistacia lentiscus L.; Quercus ilex L.